Determinants of knowledge sharing behaviors among public sector employees in northern province - Senthooran, T. (University of Jaffna, 2022)
Purpose: This study aims to investigate the antecedents of knowledge-sharing behavior among the public sector employees in Northern Province, using widely accepted social psychology theories. Methodology: This research tested a conceptual framework derived from widely accepted theories. Questionnaire data were based on a sample of 207 public sector employees from Northern Province. The suggested research model was tested by using the quantitative way of analysis (Regression analysis) and to examine the proposed hypothesis of this inquiry. Findings: The theoretical model was validated within the context of a single empirical study. The Findings provided significant statistical support for the research. This empirical study indicated that antecedents of knowledge sharing behavior significantly to knowledge sharing behavior. In total, 9 of the 7 hypothesized Impacts were supported. Research limitations: In this research due to the prevailing Covid - 19 situation the researcher has selected the snowball sampling for this study. So, future research may capture this phenomenon on this scope. Implications: This paper has attempted to furnish an understanding of knowledge sharing behavior among public sector employees. Practically, this study provides several recommendations to enhance knowledge sharing behavior. For the managerial implications, study provides insights on motivational success factors that may function as points of reference for increasing employees' active participation.
Keywords: Knowledge sharing behavior; Theory of reasoned action